(untitled) - Lê, Thị Thái Trân (Cần Thơ, 2020)
This research aimed to investigate EFL (English as Foreign Language) teachers’ choice of out-of-textbook activities for teaching speaking skills and explore the types of activities the teachers often bring into their classroom if they have chance, apart from the activities and tasks in the textbook. Besides, it aims to gain insights to the criteria that the teachers use when they select those activities. Three questions are posed: (1) What type of activities do teachers often bring into their classroomif they have a chance,apart from the activities or tasks in the textbook? (2) At what stage would they use these activities? (3) Why would they choose these activities in their speaking class? The questionnaire data were collected from 20 English teachers and the interview data from choosing randomly 5 English teachers at a private university in Can Tho city. The findings in this study have shed lights on how teachers chose and used supplementary activities for teaching speaking. Besides, the study also helps provide an understanding of the reasons why these materials, activities are brought into the classroom in speaking lessons. It shows the efforts the teachers make to design their lessons reasonably and use out of textbook materials effectively so as to create a communicative environment for their students. Based on the result of the data analysis it can be concluded that the out-of-textbook activities were integrated or modified to supplement the textbook activities and to be more effective in speaking classrooms. Additionally, it aims to supplement for what is considered as being missing in the textbook and to promote students’ interaction in speaking.
Keywords: English,Tiếng Anh; Study and teaching,Dạy và học